The Gospel according to Matthew a commentary - Konradt, Matthias 1967-; Boring, M. Eugene 1935- (Waco Baylor University Press, 2020)
"An exegesis of Matthew focusing on scriptural and cultural influences that shaped the narrative of Jesus the Christ"--
Originally published in German in Göttingen: Vandenhoeck & Ruprecht, 2015
Includes bibliographical references
Keywords: Bible -- Commentaries; Kommentar